A dictionary of nursing 2026-02-15T23:31:19+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Martin, E. A. (Elizabeth A.), 1945- .); McFerran, Tanya A. (Oxford paperback reference, 2008)

(untitled)
The new editions of these best-selling and trusted dictionaries have been fully updated and revised to take account of recent developments in nursing practice and related fields